1989
DOI: 10.1103/physrevb.40.9135
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic effects in fluid-saturated poroelastic media

Abstract: The Biot theory of Quid-saturated poroelastic media is extended to include the electrokinetic effects of streaming potential and electro-osmosis in the low-frequency or "resistive" domain. The equations presented are shown to reduce to the familiar equations under steady-state conditions, where they also satisfy the Onsager reciprocity conditions. Plane-wave solutions to the linearized equations show that significant electric potentials accompany the passage of compressional waves for a broad range of material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…This is within a factor of three of the measured amplitude of 3.8 mV/m. Thus, given the uncertainty in the values of t and z, the quasi-static theory of Neev and Yeatts [1989] seems to provide a reasonable explanation for the origins of the co-seismic seismoelectric signals observed in this case.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is within a factor of three of the measured amplitude of 3.8 mV/m. Thus, given the uncertainty in the values of t and z, the quasi-static theory of Neev and Yeatts [1989] seems to provide a reasonable explanation for the origins of the co-seismic seismoelectric signals observed in this case.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 99%
“…Garambois and Dietrich [2001] reported that co-seismic seismoelectric signal strengths measured at surface were consistent with predictions based on a low frequency form of that theory. In this case, we compare our borehole measurements to an alternative model, developed by Neev and Yeatts [1989] which has received less attention in the literature. The model is simpler and less general than that of Pride and Haartsen [1996] in that it ignores electromagnetic effects and any frequency dependence of physical properties.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To study these phenomena in poroelasticity at a macroscopic scale, the average acoustic and electromagnetic fields in the presence of a complex network of capillaries must be determined. Previous models of seismoelectric phenomena in geophysics [Frenkel, 1944;Fitterman, 1978;Auriault and Strzekecki, 1981;Neev and Yeats, 1989] and colloidal chemistry [O'Brien, 1988] did not use the full set of Maxwell's equations and/or limited their scope to the lowfrequency case. They therefore failed to predict key theoretical and experimental behaviors-such as EM wave generation at a fluid-sediment interface caused by a highfrequency, incident acoustic wave-that are a robust feature in our experimental data.…”
Section: Electric Double Layermentioning
confidence: 99%
“…providing nonnegativity of the entropy production rate is also satisfied automatically [26] due to the representation formulas (36) and (37). The inequality (38) becomes equality if both the diffusion coefficients i are negligible.…”
Section: Electrokinetic Coupling Coefficientsmentioning
confidence: 99%